2021
DOI: 10.1186/s13028-021-00597-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antibodies in cerebrospinal fluid for the diagnosis of tick-borne encephalitis in dogs

Abstract: Tick-borne encephalitis (TBE) is caused by the neurotropic tick-borne encephalitis virus (TBEV). In dogs, this virus may affect the central nervous system (CNS), causing meningoencephalitis, meningomyelitis, radiculitis or any combination of these. Diagnosis of TBE relies on a combination of clinical signs of CNS disease and laboratory findings, including CSF pleocytosis and serum TBEV antibody titers. Exposure to TBEV does not necessarily cause clinical disease, and seroprevalence has been reported as high as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Afterwards, the positive samples are subjected to a virus neutralization test, which is considered as the golden standard test for flavivirus antibody detection, to eliminate potential false positive results. From 38 identified screening studies of flavivirus antibodies in animals, 19 used the Immunozym FSME IgG All Species ELISA (Progen, Heidelberg, Germany) [ 12 , 14 , 15 , 19 , 20 , 21 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ], 10 used the ID Screen WNV Competition ELISA Kit (Innovative diagnostics, Montpellier, France) [ 13 , 33 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ] and 9 used other ELISA kits [ 9 , 22 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ] as a first screening. Based on this literature study, it was decided to evaluate the performance of the Immunozym ELISA and the IDScreen ELISA in more details.…”
Section: Introductionmentioning
confidence: 99%
“…Afterwards, the positive samples are subjected to a virus neutralization test, which is considered as the golden standard test for flavivirus antibody detection, to eliminate potential false positive results. From 38 identified screening studies of flavivirus antibodies in animals, 19 used the Immunozym FSME IgG All Species ELISA (Progen, Heidelberg, Germany) [ 12 , 14 , 15 , 19 , 20 , 21 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ], 10 used the ID Screen WNV Competition ELISA Kit (Innovative diagnostics, Montpellier, France) [ 13 , 33 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ] and 9 used other ELISA kits [ 9 , 22 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ] as a first screening. Based on this literature study, it was decided to evaluate the performance of the Immunozym ELISA and the IDScreen ELISA in more details.…”
Section: Introductionmentioning
confidence: 99%
“…However, a recent study by Salat et al (2021) has also described the presence of seroconversion in experimentally infected dogs without clinical signs, and, therefore, serological results should be analysed in conjunction with the clinical signs. In addition, CSF antibodies would have been a useful test as recently reported by Alnefelt et al (2021). Only one of the deceased dogs underwent post-mortem examination, limiting the diagnosis in the other two dogs.…”
Section: Discussionmentioning
confidence: 95%
“…This finding is not surprising as the presence of the TBEV in blood and CSF has been reported as insignificant once the initial viremic phase is finished (Kaiser, 1999(Kaiser, , 2012Marriott et al, 2006;Veje et al, 2018). A recent study by Alnefelt et al (2021) has demonstrated the utility of CSF antibody analysis compared to PCR in TBEV and LIV infections. However, in the present study, a dog showed negative TBEV serology and PCR in CSF, but positive immunohistochemistry on post-mortem examination of the brain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations